INOVASI PEMBELAJARAN KURIKULUM MERDEKA MELALUI PELATIHAN PENGEMBANGAN E-COMIC BAGI GURU SDN KEBUNAGUNG II SUMENEP - Kurratul Aini; Muhammad Misbahudholam AR; Sama' Sama'; Hodairiyah Hodairiyah; Siti Arifa; Choli Astutik (LPPM Universitas Bina Bangsa, 2023)
This Community Service (PKM) activity was carried out at SDN Kebunagung II, Sumenep City District, Sumenep Regency, East Java Province. The purpose of this PKM activity is to improve teachers' ability to create learning media using technology so that teachers are able to create an active learning environment through digital comics as a learning medium in helping teachers deliver material at the Elementary School (SD) level in the Independent Curriculum, and aims to solve the problems of teachers at SDN Kebunagung II in maximizing students' digital literacy and numeracy competencies. This training activity is divided into 3 stages, namely the preparation stage, the implementation stage, and the post-implementation stage. This activity helps teachers at the elementary level, especially teachers at SDN Kebunagung II to understand the use of technology as a learning medium. Based on the results of the activity, it is known that teachers are very enthusiastic about using technology-based learning media in the form of digital comics. It can be concluded that this service activity was carried out well in accordance with the expectations of the service team and the participants, where teachers already understand how to implement technology as a form of learning media at SDN Kabunagung II